Archaeological Mapping Project - O’Keefe, Mary; Rudd, David; Hurren, Kathryn (Architectural History Aotearoa, 2021)
In light of the earthquake in Christchurch, as well as the recent ones in Wellington, the need to know the location and types of archaeological sites/themes in Wellington is important. NZHPT, combined with the Wellington Archaeological Group, Wellington Tenths Trust/Port Nicholson Block Settlement Trust, are working on a Wellington City archaeological mapping project that will have two purposes, the first being a tool that can be used in an emergency event to guide heritage experts, council, NZHPT and the equivalent of CERA, with a systematic and practical map showing the areas of high, medium, low or no archaeological risk. The second tool that will come out of this project is a mapping tool that can be used by consultants, Wellington City Council, tangata whenua, developers and other groups, on a daily basis to help identify the archaeological potential of an area in respect to proposed development or research. The project will pull together local archaeological consultants’ knowledge, tangata whenua knowledge, Wellington City Council and archival information as well as information on previous archaeological authorities and registrations held at NZHPT. We are seeking information and knowledge from people within the heritage community who can help in developing the project.